COMPARISON OF POLY ALUMINIUM CHLORIDE (PAC) AND ALUMINIUM SULPHATE COAGULANTS EFFICIENCY IN WASTE WATER TREATMENT PLANT - Nofriady Aziz; Nuradam Effendy; Kris Tri Basuki (Jurnal Inovasi Teknik Kimia, 2017)
Hospital waste water containing high organic compounds that can harm the environment if not done processing beforehand. One way to lower the price of contaminants contained in hospital wastewater is the process of physically-chemical treatment using coagulation process in the Waste Water Treatment Plant and the coagulation process requires coagulant optimally capable of reducing the organic content in the water treatment. The purpose of this research is to make the design of waste water treatment plant and compare the effectiveness of the use of poly aluminum chloride (PAC) and aluminum sulfate in water turbidity reduction of hospital waste at the Waste Water Treatment Plant design. So that at the Waste Water Treatment Plant produces effluents that comply with effluent hinted that diindentifikasikan in parameters such as BOD, COD and TSS. The WWTP design is Consist of equalization bath, bath coagulation, chlorination and sump. The study was conducted with the study of literature. Based on the research results with the use of a second dose of the coagulant optimum of 160 mg / l. The highest efficiency value to decrease BOD, COD, TSS and TDS looks at PAC coagulant aluminum sulfate compared with the percentage of 96.17%, while the PAC valued at 95% although if measured in terms of economical aluminum coagulants have more economic value namu in terms of environmental and safety the use of PAC is better than Alum. Therefore, in the coagulation process of hospital waste water is recommended to use coagulants PAC. Keywords :  Aluminum Sulfate, Coagulant efficiency, Hospital waste water, Poly Aluminium chloride